Hibah in the perspective of Islamic finance: A study on the practices among staff at Pejabat Agama Daerah Kulim (PADK) / Ain Hasanah Mohamad Sobri - Mohamad Sobri, Ain Hasanah (2025)
Hibah usually takes place in the lifetime of the grantor and does not involve violence or threats. The transfer of ownership of property is usually pure from one part to another without any consideration or reward in return. Based on previous cases, Muslims in Malaysia rarely practice hibah in this country due to not exposing themselves to the implementation of hibah and not understanding what is hibah. Therefore, this paper aims to examine the practices, challenges, and obstacles faced by staff at the Pejabat Agama Islam Daerah Kulim in managing hibah. The implementation of hibah at the Pejabat Agama Daerah Kulim is discussed in this paper to provide a clearer understanding to the community. In this study, the researcher employs qualitative data collection methods such as interviews and document analysis to complete the findings which involve five staff of Pejabat Agama Daerah Kulim, with data analysed thematically. Interviews were conducted with selected informants based on their experience and criteria in various administration areas at the Pejabat Agama Daerah Kulim. The selection of informants was carried out by the researcher to gain deeper insights into the research questions and objectives. These interview sessions were limited to the Pejabat Agama Daerah Kulim. Additionally, the document analysis method was also used by the researcher to strengthen the study's findings. The study’s findings indicate that although staff have a basic understanding of hibah, they also face various obstacles, such as the absence of standardized procedures, resource constraints, and limited public engagement. Effective strategies are therefore necessary to address these issues, emphasizing the need to enhance staff training, public education initiatives, and the establishment of a comprehensive framework to promote hibah as an essential tool in Islamic finance. This study also highlights the potential of the Pejabat Agama Daerah Kulim to serve as a central hub for promoting hibah, thereby increasing its acceptance and utilization within the Muslim community.